Video based learning vs instructor led training for optimizing personal protective equipment use to prevent Covid-19 infection- a comparative study - Asma Ansari; Uzma Urooj; Mustafa Waseem; Alveera Ihtasham (Journal of the Pakistan Medical Association, 2022)
Objective: To evaluate two different types of education and training aids to improve compliance with guidelines related to personal protective equipment in healthcare workers. Methods: The quasi-experimental study was conducted at the Department of Gynaecology and Obstetrics, Combined Military Hospital, Rawalpindi, from July 1 to December 31, 2020, and comprised healthcare personnel who were divided into two equal groups. Group A received weekly instructor-led training session of donning and doffing for two hours. Group B was assigned to watch 30-min training videos weekly. After one month, an independent instructor evaluated both the groups using validated checklists, with maximum score 8 for donning and 14 for doffing. Data was analysed using SPSS 22. Results: Of the 60 subjects, 34(56.6%) were females and 26(43.3%) were males. There were 30(50%) subjects in group A with a mean age of 35.35±5.67years, and the remaining 30(50%) were n group B with a mean age of 33.12±4.13 years. There was no significant difference in donning and doffing scores between the groups (p>0.05). Conclusion: Both types of education and training aids could be used to improve compliance with guidelines related to personal protective equipment in healthcare workers. Key Words: Covid-19, Donning, Doffing, Personal protective equipment.